Improved sprinkler irrigation layouts for smallholders - Rad, Saeed; Gan, Lei; Dai, Junfeng; Zhang, Shuaipu; Huang, Liangliang; Pan, Linyan; Taha, Mohd Raihan (International Journal of Agricultural and Biological Engineering, 2022)
Pressurized irrigation systems are economically justifiable for medium- to large-scale farms, while fewer choices are available for smallholders. The current research work provides additional options for small plots, as the only income source for low-income farmers in poorer countries, which produce a considerable portion of the agricultural products in some regions of the world. In this research, two novel layouts of a semipermanent sprinkler irrigation system, namely, clock hand (CH) and corner pivot (CP) lateral designs, were designed for a lighter irrigation system to lower the cost requirement. The new techniques were based on a quadrant/full circle movement pattern of manually pivoting laterals, with no/shorter main pipe requirements, which causes a higher system efficiency. These retrofitted layouts were examined in different farms with areas of 0.20 hm2, 0.81 hm2, 1.62 hm2, and 3.24 hm2 in Guangxi, China. This study introduced, analyzed, and compared the layouts with the widespread traditional split lateral method on technical planning, components, implementation, operation details, size optimization, performance evaluation, and economic advantages. In comparison with the traditional system, CH and CP were found to be more user-friendly and cost-effective but slightly complicated in design with higher required manual work. The results revealed a distribution uniformity (LQDU) of 81.0% to 84.0% via the catch can method, lower capital costs (35.0%-45.0%), and lower annual expenses (6.5%-9.8%) for CP and CH, respectively, compared to the split lateral method. The 0.81 hm2 and 1.62 hm2 farms were found to be the optimum farm sizes for implementation of the new methods for a 25-year project time horizon. The outcomes of this experimental work can encourage small farm owners with limited capital to apply pressurized systems for efficient irrigation and water resource sustainability.Keywords: sprinkler irrigation layout, semipermanent, smallholder, cost-effectivenessDOI: 10.25165/j.ijabe.20221502.6363Citation: Rad S, Gan L, Dai J F, Zhang S P, Huang L L, Pan L Y, et al. Improved sprinkler irrigation layouts for smallholders. Int J Agric & Biol Eng, 2022; 15(2): 30–38.